Discovering computers fundamentals : your interactive guide to the digital world - Shelly, Gary B.; Vermaat, Misty E. ;Quasney, Jeffrey J. ;Sebok, Susan L.;Freund, Steven M. (Singapore : Cengage Learning Asia Pte Ltd, 2012)
Students are guided through the latest trends in computer concepts and technology in an exciting and easy-to-follow format. Updated for currency, DISCOVERING COMPUTERS FUNDAMENTALS provides the most up-to-date information on the latest technology in today's digital world.
Basic introduction to computers -- Fundamentals of the World Wide Web and Internet -- Software for systems -- System unit components -- Understanding input and output -- Types of storage -- Types of utility programs and operating systems -- Networks and communications -- Managing a database -- Manage computing securely, safely and ethically -- Exploring information system development and programming languages -- Enterprise computing.
"This edition is licensed for sale only in the Philippines. Circulation of this edition outside of the Philippines is unauthorized and strictly prohibited."--Cover. "This edition is reprinted with license from Course Technology, a part of Cengage Learning, for sale in the Philippines only."--Title page verso.
Includes index.
Keywords: COMPUTERS